A new Meckel’s cartilage from the Devonian Hangenberg black shale in Morocco and its position in chondrichthyan jaw morphospace - Greif,Merle; Ferrón,Humberto G.; Klug,Christian (PeerJ, 2022)
Fossil chondrichthyan remains are mostly known from their teeth, scales or fin spines only, whereas their cartilaginous endoskeletons require exceptional preservational conditions to become fossilized. While most cartilaginous remains of Famennian (Late Devonian) chondrichthyans were found in older layers of the eastern Anti-Atlas, such fossils were unknown from the Hangenberg black shale (HBS) and only a few chondrichthyan teeth had been found therein previously. Here, we describe a Meckel’s cartilage from the Hangenberg black shale in Morocco, which is the first fossil cartilage from these strata. Since no teeth or other skeletal elements have been found in articulation, we used elliptical Fourier (EFA), principal component (PCA), and hierarchical cluster (HCA) analyses to morphologically compare it with 41 chondrichthyan taxa of different size and age and to evaluate its possible systematic affiliation. PCA and HCA position the new specimen closest to some acanthodian and elasmobranch jaws. Accordingly, a holocephalan origin was excluded. The jaw shape as well as the presence of a polygonal pattern, typical for tessellated calcified cartilage, suggest a ctenacanth origin and we assigned the new HBS Meckel’s cartilage to the order Ctenacanthiformes with reservations.
Keywords: Early vertebrates; Meckel’s cartilage; Anti-atlas; Morphometrics; Shape analysis; Morphospace; Hangenberg black shale; Devonian